2015
DOI: 10.6061/clinics/2015(07)01
|View full text |Cite
|
Sign up to set email alerts
|

Within-breath respiratory impedance and airway obstruction in patients with chronic obstructive pulmonary disease

Abstract: OBJECTIVE:Recent work has suggested that within-breath respiratory impedance measurements performed using the forced oscillation technique may help to noninvasively evaluate respiratory mechanics. We investigated the influence of airway obstruction on the within-breath forced oscillation technique in smokers and chronic obstructive pulmonary disease patients and evaluated the contribution of this analysis to the diagnosis of chronic obstructive pulmonary disease.METHODS:Twenty healthy individuals and 20 smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The correlations between WT and impedance were independent of Ai, and vice versa, according to the partial correlation analysis. Peribronchial fibrosis and consequent remodeling of airway tissue associated with COPD progression reduces airway compliance, which may result in a decrease in respiratory reactance 30 31 . The correlation between thickening of airways walls and respiratory reactance observed in the present study was compatible with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations between WT and impedance were independent of Ai, and vice versa, according to the partial correlation analysis. Peribronchial fibrosis and consequent remodeling of airway tissue associated with COPD progression reduces airway compliance, which may result in a decrease in respiratory reactance 30 31 . The correlation between thickening of airways walls and respiratory reactance observed in the present study was compatible with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Third, static CT images obtained at full-inspiration could not account fully for dynamic changes in the lungs during tidal breathing. Airway caliber collapses in the expiratory phase because of low elastic recoil pressure due to parenchymal destruction (emphysema) 32 33 , which is thought to be associated with within-breath difference in respiratory impedance 17 31 34 . Time-series analyses of airways could provide further insights into respiratory impedance.…”
Section: Discussionmentioning
confidence: 99%
“…In recent work from our group, Silva et al 62 , 63 evaluated the diagnostic accuracy of monofrequency oscillometric pulmonary function in smokers and patients with COPD. These studies evaluated mean within-breath respiratory impedance ( Z rs ) during inspiration ( Z i ), expiration ( Z e ), and respiratory cycle dependence (∆ Z rs = Z e – Z i ).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that COPD induces respiratory cycle dependence, which is proportional to the degree of airflow obstruction. Another important finding of these studies 62 , 63 is that the Z rs observed in different phases of the respiratory cycle may be useful in the detection of COPD.…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory impedance, as measured at airway opening is widely regarded as a sensitive indicator of pulmonary pathology in lung disease [ 4 , 11 15 ]. Impedance measurements are typically analyzed using inverse modeling, where spectral data are fit to simple mechanical models with a small number of free parameters.…”
Section: Introductionmentioning
confidence: 99%